PELAKSANAAN PENYIDIKAN TERHADAP TINDAK PIDANA PEREDARAN OBAT KADALUARSA OLEH BADAN PENGAWAS OBAT DAN MAKANAN - Gunawan Widjaja; Taupik Alpiyandi (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2021)
The consumer rights mentioned above show that the issue of consumer comfort, security, and safety is the most important thing in consumer protection issues. Legal responsibility in the event of consumer losses due to expired drugs is the obligation of consumers to read or follow information instructions and procedures for using or utilizing drugs for safety and security, it is important to get regulation. The importance of this obligation is because often business actors have conveyed a clear warning on the label of a product/drug, but consumers do not read the warning that has been delivered. The regulation of this obligation gives the consequence that the business actor is not responsible if the consumer in question suffers a loss due to neglecting the obligation. This research was made using normative research methods, because this research is supported by data obtained from the literature by collecting secondary data in the form of primary legal materials, secondary legal materials and tertiary legal materials. The primary legal materials for this thesis are the 1945 Constitution of the Republic of Indonesia, which was amended IV and Law Number 8 of 1999 concerning Consumer Protection. After the data is collected, the data is processed by verifying and validating the validity of the data. Data analysis was carried out by applying the syllogistic way of thinking and deductive methods in order to find conclusions or answers from the formulation of the problem.